Utilization of Online Village Administration Services: Training on the use of Cihuni Village Website Features - Jansen Wiratama; Rudi Sutomo; Raymond Sunardi Oetama; Samuel Ady Sanjaya; Santo Fernandi Wijaya (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
Public administration services are important for urban and rural communities. With a large population, it is difficult for administrative service processes using conventional methods to run optimally, so they need to be transformed into digital form. Current technology should support optimizing administrative services from village officers to the community. However, limitations related to the use of technology still need to be solved by village officers. Therefore, training is needed for village officers in using administrative service features via the Cihuni village website resulting from previous research. This training activity was carried out in Cihuni Village, a village supported by Multimedia Nusantara University (UMN). The training process involved the UMN Lecturer Team as community outreach members and Cihuni Village officers. This community outreach activity increases the understanding of village officials regarding using the Cihuni village website, which has various features for public administration services.